Participation and Distribution of Time in Daily Activities of Men and Women Working in the Labor Market in Mexico - Sosa Márquez, María Viridiana; Román Reyes, Rosa Patricia (Sociedad y Economía, 2015)
The increased participation of women in the labor market and the declining fertility rates show a change in gender roles. This transformation has not meant a readjustment of tasks between family members. This raises an imbalance between partners, causing overload and disadvantages for women because of the difficulty of reconciling work and family. This study presents an estimate of participation and distribution of time in daily activities by sex, with the Encuesta Nacional sobre Uso del Tiempo 2009, to approach the social organization among men and women that have a paid work in Mexico. The results show persistent imbalances and the need of public policies addressing this issue.